Replication of Association of a Novel Insulin Receptor Gene Polymorphism with Polycystic Ovary Syndrome - Goodarzi, Mark O. (2011)
OBJECTIVE: To evaluate association with polycystic ovary syndrome (PCOS) of 295 variants in 39 genes central to metabolic insulin signaling and glycogen synthase kinase-3β (GSK-3β) regulation, followed by replication efforts. DESIGN: Case-control association study, with discovery and replication cohorts. SETTING: Subjects were recruited from reproductive endocrinology clinics, controls were recruited from communities surrounding the University of Alabama at Birmingham and Erasmus Medical Center. PATIENTS: 273 cases with PCOS and 173 controls in the discovery cohort; 526 cases and 3585 controls in the replication cohort. All subjects were Caucasian. INTERVENTIONS: Phenotypic and genotypic assessment. MAIN OUTCOME MEASURES: 295 SNPs, PCOS status. RESULTS: Several SNPs were associated with PCOS in the discovery cohort. Four insulin receptor (INSR) SNPs and three insulin receptor substrate 2 (IRS2) SNPs associated with PCOS (P<0.05) were genotyped in the replication cohort. One INSR SNP (rs2252673) replicated association with PCOS. The minor allele conferred increased odds of PCOS in both cohorts, independent of body mass index (BMI). CONCLUSIONS: A pathway-based, tagging SNP approach allowed us to identify novel INSR SNPs associated with PCOS, one of which confirmed association in a large replication cohort.